PECULIARITIES AND PERSPECTIVES OF DEVELOPING BARRIER-FREE TOURISM IN RUSSIA - AGAMIROVA, Ekaterina Valerievna; AGAMIROVA, Elizaveta Valerievna; ADASHOVA, Tatiana Alekseevna; KOSAREVA, Natalia Viktorovna; KONOVALOVA, Elena Evgenievna (Journal of Environmental Management and Tourism, 2016)
The article is devoted to the problem of inclusive tourism in Russia that is urgent in the contemporary world. The article considers issues related to the peculiarities of organizing the infrastructure of barrier-free tourism. Special attention is paid to the creation and exploitation of the environment that is accessible for the disabled in the city of Sochi. The authors of the article describe the Sochi Olympic facilities and possibility of their further use in the organization of sports and event tourism.
Keywords: inclusive tourism; tourism for the disabled; non-mobile groups of people; Sochi; barrier-free environment